Genetic analysis of schizophrenia and bipolar disorder reveals polygenicity but also suggests new directions for molecular interrogation. (February 2015) - Neale, Benjamin M; Sklar, Pamela
Highlights: Genetic analysis of schizophrenia and bipolar disorder is uncovering a wide array of significant effects. These results support a model of polygenic inheritance for both diseases with genetic effects spanning the allele frequency spectrum. The results from common and rare variation suggest a role for biological pathways such as calcium channel signaling and synaptic function in disease pathogenesis. Abstract : Over the last few years, genetics research has made significant strides in identifying many risk factors for schizophrenia and bipolar disorder. These risk factors include inherited common single nucleotide polymorphisms, copy number variants, and rare single nucleotide variants, as well as rare de novo variants. For all variants, the common theme has been that of polygenicity, meaning that many small genetic risk factors influence risk in the population and that no gene or variant on its own has been shown to be fully deterministic of schizophrenia or bipolar. When taken together, biological themes that have emerged including the importance of synaptic function and calcium signaling. This has implications for our understanding of the biological underpinnings of these diseases.